Five young δ Scuti stars in the Pleiades seen with Kepler/K2. Issue 4 (29th January 2022) - Murphy, Simon J; Bedding, Timothy R; White, Timothy R; Li(李亚光), Yaguang; Hey, Daniel; Reese, Daniel; Joyce, Meridith
ABSTRACT: We perform mode identification for five δ Scuti stars in the Pleiades star cluster, using custom light curves from K2 photometry. By creating échelle diagrams, we identify radial and dipole mode ridges, comprising a total of 28 radial and 16 dipole modes across the five stars. We also suggest possible identities for those modes that lie offset from the radial and dipole ridges. We calculate non-rotating stellar pulsation models to verify our mode identifications, finding good agreement within the age and metallicity constraints of the cluster. We also find that for all stars, the least dense models are preferred, reflecting the lower density of these oblate, rotating stars. Three of the five stars show rotationally split multiplets. We conclude that the sample shows promise for asteroseismic rotation rates, masses, and ages with rotating models in the future. Our preliminary modelling also indicates some sensitivity to the helium abundance.